Southeast Asian houses : expanding tradition - Ju, Seo Ryeung (Seoul Selection, 2017)
Southeast Asian architecture tends to be generalized under one umbrella due to the countries' common geographical, climatic, and historical context. However, Southeast Asian countries are dissimilar due to their ethnic and religious differences, which led to each country's own subtle characteristics in housing. In order to identify the commonality and diversity among Southeast Asian architecture, details of the architectural forms have to be carefully analyzed. This book begins with an introductory section about housing culture in Southeast Asia as a whole and then examines the traditional hous.